Ambientes virtuais de aprendizagem e redes sociais : sobre complementos, realizações e possibilidades - Santana, Edie Correia (2014)
Various sectors of society have been impacted by the rise and the constant advances of Information and Communications Technologies, indicating major changes in the ways of teaching, learning, communicating, relating to each other and living in society. The educational sector was impacted by these changes, especially those related to the emergence of systems to support interaction among people at a distance, such as virtual learning environments and social networks. With these systems, new spaces emerge where students discuss issues, express opinions and seek materials. Thus, this research aims to analyze the context and the reasons that led to the establishment of the group UFMT - Japan, the social network Facebook, by the students of Pedagogy Course in the Agreement Brazil / Japan and what is the relationship with the VLE Moodle Course. This research used a qualitative approach with exploratory and descriptive methodology. As instruments of data collection, simple observations , mixed questionnaires and interviews were used. The subjects were students of Pedagogy Brazil/Japan Agreement, components of the UFMT-Japan Facebook group. The results showed that the students perceived that the organization of the environments and the information therein are different and this made them participate of the two environments. Regarding the characteristics of the environments, the students characterized the VLE Moodle as an official and formal place, in which it was possible to connect in order to perform the activities of the course. However, the UFMT-Japan group was seen as a more flexible space, where they could talk about various subjects. However, there was the perception that the group had a focus directed to the theme of Education. Thus, according to the results of the study, the UFMT-Japan group can be understood as a complementary space with a new, more informal, flexible configuration, with another focus, with new forms of sociability that can encourage participation and interactions among students.